The Constitutionality of the Administrative Border and Identity Commission - Kitaw, Tgegne Zergaw (Bahir Dar University Journal of Law, 2023)
In Ethiopia, in the past years, many questions have been raised in relation to claims of identity, self-administration, and administrative border that have led the country to a bloody conflict, instability, disruption of peace and security, and anarchy. As part of a solution for these problems, the federal government has enacted a law that established the Administrative Border and Identity Commission. Following the enactments of the establishment proclamation, there is strong opposition against the establishment of the commission by claiming that is not constitutional to establish such kinds of commission in the presence of other duly and constitutionally established institutions. Even one region of the country has passed a decision that makes the proclamation non-effective in that particular region claiming that it conflicts with the constitution. Therefore this study aims at assessing the constitutionality of the Administrative Border and Identity Commission and to evaluate the critics against it. To do this the researcher examined and analyzed the Constitution of the Federal Democratic Republic of Ethiopia, other relevant laws of the country and the existing institutional practice. Accordingly, the findings of the study revealed that the critic against establishing the commission that solely bases on its conflict with the Constitution is unacceptable and baseless. It is because of the fact that the commission does not have the effect of replacing the existing duly established constitutional institution as long as such constitutional the House of Federation, the institution constitutionally mandated with the issues in discussion, has still the final say over the recommendation of the Commission. Except for few gaps and some minor problems, the establishment of the Commission is not in conflict with the Constitution rather than supporting and strengthening the constitutional mechanisms. Hence, if properly utilized and duly constituted, the Commission will play enormous roles in the national efforts to find a lasting solution for those questions and conflicts by investigating the root causes of the problem and providing research based recommendations.